Perbandingan Komplikasi Vaskular Antara Pendekatan Arteri Radial dengan Femoral Pada Intervensi Koroner Perkutan Primer yang Memakai Eptifibatide - Surya Hafidiansyah; Yoga Yuniadi; Sunarya Soerianata (Jurnal Kardiologi Indonesia, 2011)
Background.The transfemoral approach for percutaneous coronary intervention (PCI) has the complications in vascular access site more than transradial approach. Risk of vascular complications will increase in using eptifibatide. Methods.. This is a prospective cross sectional study involving 52 STEMI patients qualified to primary PCI. 26 patients in transfemoral approaches and 26 patients in transradial approaches. In these two groups, we compare the incidence of vascular complications such as bleeding, arteriovenous fistula, pseudoaneurysm and artery occlusion.Results. From the 52 subjects of this study, found 94.2% men and 5.8% women, mean age 54.3 ± 9.9 years with the highest risk factors were smoking (67.3%), hypertension (51.9%), dyslipidemia (34.6%), diabetes (30.8%) and family history (11.5%). There were no significantly statistic relationship between duration of puncture and PCI procedures between the two groups. Incidence of vascular complications occurred in the femoral group (19.1% vs. 0), consist of arteriovenous fistula (11,5%), pseudoan-eurysm (3,8%), and minor bleeding (3,8%). Minor bleeding occurred in female subject with age 77 years.Conclusion. There was no significant difference in vascular complications between transfemoral approaches with transradial approaches on the Primary PCI